A new generation of aprotic yet Bronsted acidic imidazolium salts: effect of ester/amide groups in the C-2, C-4 and C-5 on antimicrobial toxicity and biodegradation - CONNON, STEPHEN (My University, 2013)
Imidazolium Brønsted acidic catalysts substituted with ester/amides have been assessed for both antimicrobial toxicity and biodegradation. Low toxicity to a screen of 20 microbial strains (12 fungi and 8 bacteria) was demonstrated. Imidazolium salts incorporating either ester or amide groups at N-1, C-2, C-4 and C-5 did not pass the readily biodegradable test (ISO 14593). Catalyst selection based on Traffic Signal Light classification of performance, (eco)toxicity, and efficient synthesis is described.
PUBLISHED
Keywords: Brønsted acidic catalysts